An exploration of staff and prisoner experiences of a newly commissioned personality disorder service within a category B male establishment. Issue 3 (8th August 2016) - Hadden, Jennifer Marie; Thomas, Susan; Jellicoe-Jones, Lorna; Marsh, Zoe
Abstract : Purpose: – The purpose of this paper is to explore staff and prisoner experiences of a newly implemented Personality Disorder Service (PDS) within a category B male establishment. Design/methodology/approach: – A semi-structured interview was used to explore the experiences of seven male category B PDS prisoners and eight PDS members of staff (four National Health Service (NHS) clinical staff and four prison service staff) from a multi-disciplinary team (MDT). Interviews were transcribed verbatim and thematic analysis was completed. Findings: – Prisoner sample: one overarching theme "environment" organised two themes: "enabling factors" and "disabling factors" which had a subtheme "integrating men who have sexually offended onto the unit". Another theme "opportunities for self-development" was identified. Staff sample: an overarching theme "environment" organised two themes: "enabling factors" and "disabling factors". An overarching theme "multi-disciplinary working" organised two themes: "working in partnership" and "cultural differences in working practices". Two further themes were: "professional development" and "stressors". Research limitations/implications: – This study focused on a small sample of staff and prisoners and their experiences of a newly implemented PDS. In addition, both staff and prisoners volunteered to take part in the study, and therefore may not be a representative sample. Consequently the results cannot be generalised to other establishments or PD services. Practical implications: – Staff and prisoner experiences indicate that a multi-disciplinary approach to personality disorder services is desirable and can be effective. Prisoners are gaining experiences of positive therapeutic relationships with staff and hope that their experiences of the PDS will reduce their risk of reoffending. Staff experiences indicate that the integration of two services presents challenges and that they are working to overcome these. It may be advantageous for the impact of cultural differences within a MDT to be explored further. Originality/value: – This is the first study that explores the experiences of the MDT and prisoners of the newly implemented PDS. The PDS forms part of the new development under the National Offender personality disorder pathway.